Building Blocks for a Model for using EDI and ERP to Improve Supply Chain Performance in Ugandan PDEs - Violah, Mpangwire (Journal of Economics and Behavioral Studies, 2023)
The study’s overarching goal is to provide a theoretical foundation for the integration of EDI and ERP systems into Ugandan procurement and disposal entities’ supply chains to optimize their performance. A design science approach was used as a research strategy and for data collection; a cross-sectional survey using qualitative techniques, including in-depth interviews was employed. From the findings, a model was developed for data visualization, report production, analytics, and transformation. This study therefore provides an in-depth evaluation of the effectiveness of procurement and disposal organizations in Uganda with the help of EDI and ERP technologies to enhance supply chain management.